Greek–American relations in the Yom Kippur War concurrence - Kallivretakis, Leonidas (The Historical Review/La Revue Historique, 2014)
This article suggests that there is no hard evidence supporting the conspiracy theory that Georgios Papadopoulos’ dictatorial regime was overthrown by the United States in 1973, because the Greek junta leader refused to assist their supply effort in support of Israel during the Yom Kippur War.